IMPROVING STUDENTS’ WRITING SKILL OF RECOUNT TEXT THROUGH DIARY WRITING AND PEER EDITING TECHNIQUE - Rani Autila; Melati Theresia (Universitas Negeri Padang, 2018)
This research investigated the students’ writing skill on Recount Text at Session 2016 A English Department of STKIP PGRI West Sumatera. Some of them had difficulties in organization, content, grammar, mechanic, and vocabulary. Then, they really need lecturers’ correction in every step of their writing process. Therefore, the independent writing should be applied in each part of the writing process. Especially, in editing process the students have to be independent in order to increase their sensitivity on their writing product. Therefore, the researcher applied Diary Writing and Peer Editing Technique as the focus of research to solve this problem. The purposes was to find whether Diary Writing and Peer Editing Technique can improve students’ writing skill on Recount Text. The methodology of research is a classroom action research (CAR). This research was conducted in one cycle, which has six meetings. The researcher was helped by two collaborators. Researcher used writing test, observation checklist, and field note, as the instruments. The findings of the research showed that the students’ writing skill of Recount Text improved through Diary Writing and Peer Editing Technique. The implications related to this research the lecturers are suggested to use Diary Writing and Peer Editing Technique to help students to be independent writer and for the next researcher to use this technique in others kinds of texts.